Effects of closure versus non-closure of the visceral and parietal peritoneum at cesarean section: does it have any effect on postoperative vital signs? A prospective randomized study. (18th April 2017) - Kurek Eken, Meryem; Özkaya, Enis; Tarhan, Tuba; İçöz, Şeyma; Eroğlu, Şebnem; Kahraman, Ş. Tuğba; Karateke, Ateş
Abstract: Objective : To investigate the effect of peritonization at cesarean section on postoperative vital signs which was thought to be an indirect finding secondary to increased sympathetic activity originated from pain caused by stretched peritoneum. Methods : One hundred and thirty-three pregnant women were randomized to four groups; Closure of parietal peritoneum only (group 1; n  = 32), closure of visceral and parietal peritoneums (group 2; n  = 32), no closure of peritoneums (group 3; n  = 32) and closure of the visceral peritoneum only (group 4; n  = 32). All participants were monitored for blood pressure, pulse activity and hourly urinary output during the first postoperative 24 h. Postoperative pain was measured using a Visual Analogue Scale 6th and 24th hours after surgery. Return of bowel function was measured from the end of the operation to the first passage of flatus. Operating time, pre- and postoperative hemoglobin, postoperative complications, length of hospital stay and postoperative urine osmolarity were noted. Results : The mean surgery duration was significantly longer in group 2. Diuresis was found significantly decreased in group 2. Pulse rate and systolic and diastolic blood pressure were significantly higher in group 2. Closure of both peritoneums was associated with higher post-operative pain as assessed using Visual analogue scale score analyses in group 2. Conclusion : Both visceral and parietal membrane closure in cesarean section should be avoided in women with hypertensive disorders, renal function abnormalities and autonomic dysfunction because of increased postoperative pain and associated sympathetic overactivity.